SIMILARITIES AND DIFFERENCES OF NATIONAL CONCEPTS IN UZBEK AND ENGLISH PROVERBS - Jumanazarova Adiba (Western European Studies, 2025)
This article analyzes the similarities and differences of national concepts reflected in Uzbek and English proverbs. Proverbs are among the important linguistic units that express a nation’s worldview, culture, and values. The study compares shared and nationally specific features in the two nations’ thinking through concepts such as “labour,” “homeland,” “family values,” and “wisdom and intellect.” As a result, the research reveals the distinctive aspects of national spirit, attitudes toward life, values, and moral perspectives in both languages
Keywords: Proverb; national concept; national conceptworldview